Regional Innovation Systems: Current Discourse and Challenges for Future Research - David Doloreux; Saeed Parto (European Regional Science Association (ERSA), 2004)
In recent years, the concept of Regional Innovation Systems has evolved into a widely used analytical framework generating the empirical foundation for innovation policy making. Yet, the approaches utilizing this framework remain ambiguous on such key issues as the territorial dimension of innovation, e.g., the region, and the apparently important role played by “institutions” or the institutional context in the emergence and sustenance of regional innovation systems. This paper reviews and summarizes the most important ideas and arguments of the recent theorizing on regional innovation systems to provide the basis for a critical examination of such issues as (1) definition confusion and empirical validation; (2) the territorial dimension of regional innovation systems; and (3) the role of institutions. Key-words: Regional innovation systems, institutions, regions, research, policy JEL CODES: O31, R58
Keywords: O31; R58; 330